The Case for the Historical Simmel - Podoksik, Efraim (Simmel Studies)

(untitled) (Edizioni ETS, 2022)
There is a gap between the particulars ofour scholarly knowledge about Georg Simmel and our image of him as a mind in its totality. The existing paradigmatic interpretations of Simmel's thought as a whole are often outdated and driven by anachronistic motivations. The task of the historian is to update these paradigms on the basis of our better and broader knowledge of Simmel and his contexts. My book is one such attempt. The paradigm it puts forward may help us to discard the familiar stereotypes of Simmel, while offering a more nuanced understanding of the main parameters of his thought and its development. It can also serve as a foundation for future non-historical studies of Simmel.